Efforts To Prevent And Eradicate Money Laundering By The North Sumatra Financial Services Authority (Ojk) - Siregar, Reza Ananda; Lubis, Risyad Fakar (LEGAL BRIEF, 2025)
This study aims to analyze efforts to prevent and eradicate money laundering crimes (TPPU) carried out by the North Sumatra Financial Services Authority (OJK) and compare the authority and effectiveness of the OJK in preventing and eradicating anti-money laundering with the Financial Transaction Reporting and Analysis Center (PPATK). The research method used is qualitative with a case study approach and data collection through interviews, documentation, and analysis of related regulations. The results of the study show that the North Sumatra OJK has implemented various strategic steps in preventing and eradicating anti-money laundering through strict supervision of financial services institutions and the implementation of anti-money laundering policies. However, the authority of the OJK is still limited compared to PPATK which has broader authority in reporting and analyzing suspicious financial transactions. However, the collaboration between OJK and PPATK plays a very important role in increasing the effectiveness of preventing and eradicating trafficking in the North Sumatra region. This study provides recommendations for strengthening coordination and increasing the capacity of the OJK to strengthen the supervisory function and law enforcement against money laundering crimes.